PERSEPSI WISATAWAN TERHADAP KUALITAS PELAYANAN STARBUCKS COFFEE DI BANDARA NGURAH RAI BALI - Swastika P, Putri; Mahagangga, I Gst. Agung Oka (JURNAL DESTINASI PARIWISATA; Vol 4 No 2 (2016): VOL 4, NO 2 (2016): (JULY - DECEMBER) JURNAL DESTINASI PARIWISATA, 2016)
Consistency of service and product quality continue to be pursued by Starbucks Coffee as one of popular tenants at Drop Off Zone I Gusti Ngurah Rai Bali Airport, to provide a good service for passengers, especially the tourists in order to obtain a positive impression during their presence at Bali Airport. However, there has been no absolute survey of tourist’s feedback, which is required to monitor and improve the performance of the team. The research aims to determine tourists’ perception toward the product and service quality of Starbucks Bali Airport, with the result that management will acquire useful information. The data sources in this study are primary and secondary data, which are collected through literature study, observation, interview, and questionnaires. The sample is selected using accidental sampling technique, while the quantitative data from questionnaires are analyzed using a Likert scale and described qualitatively. The result of the study shows that perception of tourists toward the quality service of Starbucks Coffee Bali Airport obtains the total score of 417 which is classified as ‘good’ category. Dimension of reliability is the most preferential aspect with acquisition attitude score of 4.27 comes in the ‘excellent’ category; otherwise the worst aspects are the dimensions of responsiveness with attitude score result of 4.14 and classified in ‘good’ categories only. Speed of service comes in the major variable with score of 4.52 which can be categorized as ‘excellent’ otherwise, the quality of free Wifi obtained the lowest score of 3.67, where 8 tourists rate ‘poor’ and 4 tourists mark ‘terrible’ to this variable.
Keywords: tourists, perception, service quality, Starbucks Coffee.